1980
DOI: 10.1083/jcb.87.1.297
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-dependent recycling of synaptic vesicles at the frog neuromuscular junction.

Abstract: Frog cutaneous pectoris muscles were treated with low doses of crude black widow spider venom (BWSV) or purified a-latrotoxin, and neuromuscular transmission, quantal secretion, changes in ultrastructure and uptake of horseradish peroxidase (HRP) were studied. When these agents were applied to muscles bathed in a Ca'-free solution with 1 mM EGTA and 4 mM Mg2+ , the rate of quantal secretion rose to high levels but quickly subsided ; neuromuscular transmission was totally and irreversibly blocked within 1 h. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
164
3

Year Published

1984
1984
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 222 publications
(177 citation statements)
references
References 24 publications
10
164
3
Order By: Relevance
“…3a, these calcium imaging experiments demonstrate that c~-latrotoxin exerts effects on astrocytes that are similar to the toxin's actions on neurons, c~-latrotoxin stimulates an increase in basal release from neurons in the presence and absence of external calcium ions [25,26]. In the absence of external calcium ions transmitter release is stimulated through a direct induction of exocytosis.…”
Section: I Parpura Et Al/febs Letters 360 (1995) 266 270mentioning
confidence: 76%
See 3 more Smart Citations
“…3a, these calcium imaging experiments demonstrate that c~-latrotoxin exerts effects on astrocytes that are similar to the toxin's actions on neurons, c~-latrotoxin stimulates an increase in basal release from neurons in the presence and absence of external calcium ions [25,26]. In the absence of external calcium ions transmitter release is stimulated through a direct induction of exocytosis.…”
Section: I Parpura Et Al/febs Letters 360 (1995) 266 270mentioning
confidence: 76%
“…In neurons a similar decline in transmitter release has been shown when c~-latrotoxin is applied in calcium-depleted saline. Parallel electron microscopy has indicated that this is due to a depletion of the vesicles in the nerve terminal [25,26]. Similar effects of ~-latrotoxin in neurons and astrocytes raises the possibility that the transmitter release mechanisms of these two cell types share some fundamental properties.…”
Section: I Parpura Et Al/febs Letters 360 (1995) 266 270mentioning
confidence: 84%
See 2 more Smart Citations
“…Quantal secretion causes the changes in membrane potential that excite the postsynaptic cell, and transmission at a synapse is critically dependent upon this mechanism of release. The vesicle hypothesis holds that each quantum is confined within one of the synaptic vesicles that populate the nerve terminal and is released by exocytosis when the membrane of that vesicle fuses with the axolemma at one of the many specialized regions called "active zones" (8,13,51).A number of workers have shown that at frog neuromuscular junctions vesicles fuse with the axolemma of stimulated 1386 terminals and some of the remaining vesicles become labeled with extracellular tracers (9)(10)(11)25). Although these observations indicate that vesicles fuse with and are recovered from the axolemma when quanta are actively secreted, the slowness of chemical fixation precludes demonstrating that vesicle fusion and transmitter release are coincident.…”
mentioning
confidence: 99%